UJI KETAHANAN SAHAM VALUE DAN GROWTH INDUSTRI FOOD & BEVERAGES PADA BUSINESS CYCLE INDONESIA PERIODE 2012—2016 - Reinandus Aditya Gunawan; Valencia Priska (Jurnal Akuntansi, 2019)
The business cycle is a significant factor in the Indonesian economy because by observing the business cycle we can predict whether an economy will rise or fall within a given period. Business cycle can be reviewed by looking at composite leading indicator or commonly abbreviated as CLI. CLI in this study also examined how the relationship between the business cycle with the movement of stock prices in Indonesia. The food & beverages industry sector is selected with the consideration that the industry sector is resilient to all conditions in the business cycle. The result of this research is because CLI have positive relationship with return value stock and return from growth stock hence can be concluded that change of business cycle in Indonesia will bring change also for return value and return growth stock. However CLI has an effect but not significant for return value stock and return growth stock, this means stocks of food & beverages industry sector is quite resistant in the face of business cycle that happened in Indonesia.